If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 2ln(x) = 0 Multiply ln * x 1 + 2lnx = 0 Solving 1 + 2lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2lnx = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2lnx = 0 + -1 2lnx = 0 + -1 Combine like terms: 0 + -1 = -1 2lnx = -1 Divide each side by '2nx'. l = -0.5n-1x-1 Simplifying l = -0.5n-1x-1
| -8p-2p=16-6p | | 3(z-63)=87 | | -27=-3(4m-1)+6(-8m+5) | | -8-7+y=-5(y+3) | | -5x=16-8y | | x(2+3)=21 | | 8/12=6x | | 3x^3-5x^2-9x+45=0 | | 11n^2-33n+22=0 | | 10x=-10+5x | | -4(x+7)=-44 | | x/2=1-x/4 | | 5x^2-15x+9=2 | | 70=15x-20x | | (5k+2)(2k-3)=o | | 115+13x=-116+20x | | 280-195= | | 5r+6r=4r+7r | | 5z=-3z+7 | | 5(2.9+m)=8.3whatism | | 7x+1+5x+8=162 | | -5y-3=32 | | -6+4x+4x=10 | | 3(w-5)=9 | | 11+4n=27 | | -6+12-22=x | | 5y+x+6=0 | | 35xy^3-5xy= | | 3-2i/4i | | 120=50-2x | | 1n=1 | | 7f=1/12 |